Ceramics from the Alcazar Palace in Seville (Spain) dated between the 11th and 15th centuries: Compositions, technological features and degradation processes. Issue 15 (December 2015) - Garofano, I.; Robador, M.D.; Perez-Rodriguez, J.L.; Castaing, J.; Pacheco, C.; Duran, A.
Abstract: For the purpose of chemical characterization, a selection of 29 ceramic fragments from the 11th to 15th century has been made from materials excavated in the Seville Alcazar Palace. The PIXE elemental analysis results indicated that the ceramic bodies can be divided into four groups. The XRD identification of the phases present in the bodies revealed differences in the firing temperatures. The PIXE analysis of the glazes revealed variable PbO and SnO2 contents. The latter component was not detected in all the glazes. Cu, Co, Mn, Fe and Sb elements were associated with green, blue, black and yellow colours, respectively. Some glazes were covered by iridescent layers constituted by lead carbonate and phosphates due to alteration of the glazes. It was also possible to detail the microstructure and composition of the ultimate surface layers responsible for the lustre effect observed in two of the ceramic samples using PIXE and Rutherford backscattering spectrometry (RBS).